1999
DOI: 10.1111/1468-2362.00034
|View full text |Cite
|
Sign up to set email alerts
|

Should Banking Supervision and Monetary Policy Tasks be Given to Different Agencies?

Abstract: This paper adds some new arguments to the thesis that the responsibility for banking supervision should be assigned to an agency formally separated by the Central bank. We also provide some additional evidence on the macro and microeconomic performance of OECD countries whose banking systems are classi ed according to the regulatory regime in place. We nd that the in ation rate is considerably higher and more volatile in countries where the Central bank acts as a monopolist in banking supervision. Besides, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…It is recommended that banking supervision should be assigned to an agency formally separated from the central bank because the inflation rate is higher and more volatile in countries where the central bank acts as a monopolist regulator. Not all countries can afford deposit insurance, especially those with weak banks and regulators (Di Noia& Di Giorgio, 1999).…”
Section: Related Literaturementioning
confidence: 99%
“…It is recommended that banking supervision should be assigned to an agency formally separated from the central bank because the inflation rate is higher and more volatile in countries where the central bank acts as a monopolist regulator. Not all countries can afford deposit insurance, especially those with weak banks and regulators (Di Noia& Di Giorgio, 1999).…”
Section: Related Literaturementioning
confidence: 99%
“…There has been little empirical examination of these arguments for and against the central bank supervising banks, but that which does exist generally seems to support the benefits of a narrower focus for the central bank that does not include bank supervision. Using cross-country data, Schoenmaker (1995), andDi Noia andDi Giorgio (1999) find a positive correlation between the rate of inflation and the central bank having responsibility for both monetary policy and supervision. Goodhart and Schoenmaker (1995) point out that independent central banks, which are much better at fighting inflation, are also more likely not to have responsibility for banking supervision.…”
Section: Safety Soundness and Systemic Stabilitymentioning
confidence: 99%
“…Arguments in favor of the separation of these two functions have mostly revolved around the possibility of conflicts of interest (for instance, see Goodhart and Schoenmaker, 1993;Di Noia and Di Giorgio, 1999). Goodhart and Schoenmaker (1993) suggested that such conflicts of interest may occur due to the different objectives, economic models, and preferences involved in macroeconomic and microeconomic policy-making process, as well as administrative complications.…”
Section: Literature Reviewmentioning
confidence: 99%